Just Urban Design The Struggle for a Public City - Goh, Kian; Loukaitou-Sideris, Anastasia; Mukhija, Vinit (Urban and Industrial Environments, 2022)
Contributions by urban planners, sociologists, anthropologists, architects, and landscape architects on the role and scope of urban design in creating more just and inclusive cities. Scholars who write about justice and the city rarely consider the practices and processes of urban design, while discourses on urban design often neglect concerns about justice. The editors of Just Urban Design take the position that urban design interventions have direct and important implications for justice in the city. The contributions in this volume contextualize the state of knowledge about urban design for justice, stress inclusivity as the key to justice in the city, affirm community participation and organizing as cornerstones of greater equity, and assert that a just urban design must center and privilege our most marginalized individuals and communities. Approaching spatial and social justice in the city through the lens of urban design, the contributors explore the possibility of envisioning and delivering social, spatial, and environmental justice in cities through urban design and the material reality of built environment interventions. The editors' combined expertise includes urban politics and climate change, public space, mobility justice, community development, housing, and informality, and the contributors include researchers and practitioners from urban planning, sociology, anthropology, architecture, and landscape architecture. Contributors: Rachel Berney, Rebecca Choi, Teddy Cruz, Diane E. Davis, Fonna Forman, Christopher Giamarino, Kian Goh, Alison B. Hirsch, Jeffrey Hou, Anastasia Loukaitou-Sideris, Setha Low, Matthew Jordan Miller, Vinit Mukhija, Chelina Odbert, Francesca Piazzoni, and Michael Rios